Redesigning the Structure of Republic Indonesian Defense System; An Analysis of Systems Thinking - Muhammad, Ade; Tasrif, Muhammad; Hartati, Sri (The Asian Journal of Technology Management (AJTM), 2013)
The phenomenon of Shrinking Defense Capabilities is only the tip of the iceberg of Indonesian Defense System’s problem. The root of the problem that lies beneath and outside is keep untouched. This journal is the part of the efforts to reveal the phenomenon’s structure that binding as a system. The present structure is a cause of that phenomenon and the basis of the current organization responsible for Republic Indonesia Defense sector. With the Systems thinking analysis, the research has revealed the structure that become the problem cause and give a holistic solution trough redesigning new structure based on two theories namely the Strategic-Operational Management with Vision Dissemination of Prof. Dr. Jürgen Strohhecker and the Defense System Generic Dr. Ir. Muhammad Tasrif, M.Eng and Ir. Ade Muhammad, M.Han. The logical consequences would also changing of formation of Indonesian Defense Organization. Keywords : Design, Redesigning, Defense System, System, Defense, Holistic